CD98 heavy chain as a prognostic biomarker and target for cancer treatment - Xia, Pu; Dubrovska, Anna (Frontiers in Oncology, 2023)
The SLC3A2 gene encodes for a cell-surface transmembrane protein CD98hc (4F2hc). Together with the light subunits (L-type amino acid transporters) LAT1 (SLC7A5), LAT2 (SLC7A8), and xCT (SLC7A11), CD98hc constitutes heterodimeric transmembrane amino acid transporters. It interacts with other surface molecules such as extracellular matrix metalloproteinase inducer CD147 (EMMPRIN) and integrins. Thus, CD98hc plays an essential role within a protein complex critical for tumor energy metabolism, proliferation, and migration and serves as a vital regulator of the stress response and tumor growth in different types of tumors. The elevated expression levels of CD98hc have been confirmed in various tumor entities, including head and neck squamous cell carcinoma (HNSCC), glioma, colon adenocarcinoma, pancreatic ductal adenocarcinoma and others. Furthermore, a high expression of CD98hc has been linked to prognosis and response to chemo-and radiotherapy. In this mini-review, we discuss the physiological functions of CD98hc, its role in the regulation of tumor stemness, metastasis, and therapy resistance, and the clinical significance of CD98hc as a tumor marker and therapeutic target.